Pensions and fertility: Micro-economic evidence - Alexander M. Danzer; Lennard Zyska (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
This study identifies the causal effect of pension generosity on women's fertility behavior. It capitalizes on Brazil's expansion of the pension system to rural workers, whose pension wealth subsequently more than tripled. Event study, difference-in-differences and instrumental variable methods show that the pension reform reduces the propensity of childbearing of women in fertile age by 10% in the short-run. Completed fertility declines by 1.3 children within 20 years after the reform, reducing the contribution base of the Pay-As-You-Go pension system in the long-run. The fertility response is strongest at higher birth parities, among older women and among mothers with sons.
Keywords: J13; I38; H55; D15; 330; Pension wealth; Fertility; Old-age security hypothesis; Quasi-experiment; PAYG; Brazil